THE FULFILLMENT OF NEEDS POTRAYED IN THE MAIN CHARACTERS OF ALICIA BERENSON AND THEO FABER IN THE SILENT PATIENT NOVEL - Utami, Ghina Meidiana; Nitisari, Dwi; Firmawan, Hendro (Universitas Gunadarma, 2023)
The hierarchy of needs is psychological aspect that should be fulfilled in the individual life as a motivation. The aims of this research are to discovered the types of hierarchy of needs by used Abraham Maslow theory from Alicia Berenson and Theo Faber and how they fulfilled the needs in The Silent Patient (2019) novel written by Alex Michaelides. This research used the descriptive qualitative method because the data of this research are analysed by words namely dialogues and monologues. After classified the data, the researchers found 31 data of Alicia’s needs and 32 data of Theo’s needs of 5 stages of hierarchy of needs that taken from dialogue and monologue. The result showed that only 4 of 5 Alicia Berenson needs are fulfilled namely, 10 data of physiological needs, 6 data of safety needs, 3 data of love need, and 6 data of self-esteem needs. Whereas Theo Faber successfully fulfilled 5 needs namely, 6 data of physiological needs, 6 data of safety needs, 13 data of love need, 3 data of self-esteem needs, and 4 data of self-actualization.